SOCIAL WELL-BEING, GROUP COHESIVENESS, DAN SENSE OF COMMUNITY REMAJA DI PANTI ASUHAN - Effy Wardati Maryam; Ghozali Rusyid Affandi; Ramon Ananda Pariontri (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2022)
Abstract: Social Well-Being, Group Cohesiveness, And Sense Of Adolescent Community At Orphanage. This study aims to determine the effect of social well-being and group cohesiveness on the sense of community in adolescents at the 'Aisyiyah Orphanage Sidoarjo. This research uses correlational quantitative method. The subjects in this study were teenagers who were in the 'Aisyiyah Orphanage Sidoarjo, totaling 73 children. The sampling technique used is purposive sampling. Research data were collected using a social well-being scale referring to Keyes' theory with Cronbach's alpha reliability = 0.840, group cohesiveness scale referring to Forsyth's theory with Cronbach's alpha reliability = 0.882 and sense of community scale based on McMillan and Chavis' theory with Cronbach's alpha reliability = 0.851 . Analysis of research data using product moment correlation analysis techniques and multiple regression analysis. The results showed that social well-being and group cohesiveness each had a significant relationship with the sense of community among adolescents in orphanages. As for the two, the results of the analysis show that the relationship between group cohesiveness is stronger when compared to social well being with a sense of community. Together, social well-being and group cohesiveness have a significant influence on the sense of community, with a large effect of 20.5%.